Different Adaptations: The Power of the Vampire - Mario Vrbančić; Senka Božić- Vrbančić ([sic])
Since film first established itself as pre-eminently a narrative medium there has been a long-running questioning on the nature of the connections between film and literature. Conrand’s known statement about his novelistic intention - “My task which I am trying to achieve is, by the powers of the written word, to make you hear, to make you feel – it is, before all, to make you see” (McFarlane 3) - has often been quoted by the first filmmakers who were striving to make an adaptation and explore the vast territory of the cinematic world. Some novels have been constantly adapted, and, like Bram Stoker’s Dracula (written in 1897), have created a whole genre. In this essay we will try to analyse some aspects of the adaptation of Stoker’s novel Dracula in the first preserved film version of Friedrich Wilhelm Murnaus’ Nosferatu (1922), and, one of the latest adaptations, Bram Stoker’s Dracula by Francis Ford Coppola (1992). Some differences are noticeable between the ‘original’ narrative and how its complexity produces new readings, turning Dracula into a commodity appearing on the silver screen. We shall attempt to outline the hermeneutical circle of film adaptations in which all components play an influential role in the process of adaptation as well as in a final product; further we will indicate how historical and ideological shifts influence the adaptations and the differences between them.